2019
DOI: 10.1161/strokeaha.118.018920
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler and Magnetic Resonance in Tanzanian Children With Sickle Cell Disease

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…18 The association with indirect bilirubin as well as reticulocytosis suggests that the hemolytic rate is important, although reticulocytosis may also be related to erythropoiesis in response to chronic anemia and hypoxemia. 18 Abnormal CBFV (!200 cm/s) appears to be much less common in this study and other East African cohorts 15,23 than the 10% reported in studies from the United States, where the majority of people with SCD are of West African origin. Differences in mechanisms of vascular injury in patients with SCD residing in East Africa compared with those residing in Europe or the United States may be due to differences in genetics (e.g., haplotypes), burden of infection, environmental exposures including nutrition, and access to quality health care.…”
Section: Mricontrasting
confidence: 74%
See 2 more Smart Citations
“…18 The association with indirect bilirubin as well as reticulocytosis suggests that the hemolytic rate is important, although reticulocytosis may also be related to erythropoiesis in response to chronic anemia and hypoxemia. 18 Abnormal CBFV (!200 cm/s) appears to be much less common in this study and other East African cohorts 15,23 than the 10% reported in studies from the United States, where the majority of people with SCD are of West African origin. Differences in mechanisms of vascular injury in patients with SCD residing in East Africa compared with those residing in Europe or the United States may be due to differences in genetics (e.g., haplotypes), burden of infection, environmental exposures including nutrition, and access to quality health care.…”
Section: Mricontrasting
confidence: 74%
“…The small proportion of patient with CBFV !200 cm/s could also be related to a more rapid progression of arteriopathy in East African patients. 15 In this study of asymptomatic children with SCD, those with non-normal TCD were not significantly more likely to have intracranial vasculopathy on MRA, whereas in children with stroke, Helton et al 31 found higher rates of and more severe intracranial stenosis on MRA if TCD showed low or uninterpretable MCA velocities. Those with non-normal TCD with normal intracranial MRA might have extracranial vasculopathy; future studies should include MRA of the carotid and vertebral arteries in the neck.…”
Section: Mrimentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, we focused on overt stroke, without brain imaging than could have further substratified this phenotype as ischemic or hemorrhagic, and identified subclinical infarcts, that are also found in SCD in children in Africa. 36,37 These sub-classifications could have allowed differential exploration of genetic protective and pathophysiologic risk factors, for example, variants in genes in hemolysis pathways for ischemic stroke, and variants in genes of vasculopathy, hypertension, and connective tissues pathways for hemorrhagic stroke. However, it should be noted that our focus is on a severe event (overt stroke), not on silent subclinical events, which, by definition, do not represent severe clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…4 Three-quarters of the SCA disease burden is in Africa, and Tanzania is ranked fourth globally. 5 We have been screening for stroke risk using TCD ultrasonography at Muhimbili hospital since 2004. In a study of 200 patients undergoing TCD ultrasonography, of whom 60 with TCD abnormalities had MRI scans, the prevalence of stroke was 11.5% and the presence of SCI was 37% (verbal communication).…”
Section: Background Sickle Cell Anemia Neurologic Complicationsmentioning
confidence: 99%